Bacterial Profiles and Antibiotic Susceptibility Pattern of Wound Infections admitted at Tertiary Teaching Hospital in Dhaka city (Bangladesh Journal of Infectious Diseases, 2025)
Background: Wound infections remain a significant health concern, often developing or worsening when harmful microorganisms invade the injured tissue and are complicated by antimicrobial resistance. Knowledge of the microbial profile and antibiotic susceptibility patterns is essential for effective management.Objective: The purpose of the present study was to determine the prevalence, microbial profile, and antibiotic susceptibility patterns of bacteria isolated from wound infections in patients attending ZH Shikder Women’s Medical College Hospital.Methodology: This observational study was carried out in the Department of Microbiology at Zainul Haque Sikder Medical College Hospital, Dhaka, over six months from July to December 2024. A total of 65 wound swab samples were collected from patients visiting both the outpatient and inpatient departments. Along with the samples, socio-demographic information and laboratory data, such as bacterial isolates and their antibiotic susceptibility patterns, were recorded using a standardized form. Samples were cultured on Blood agar and MacConkey agar, and organisms were identified using standard microbiological techniques. Antibiotic susceptibility testing was performed by the disc diffusion method according to CLSI guidelines.Results: Out of 64 analyzed samples, bacterial growth was observed in 70.3% cases. The majority of participants were aged 21 to 40 years, with males slightly outnumbering females. Among 45 bacterial isolates, Staphylococcus aureus was predominant (58%), followed by Pseudomonas aeruginosa (17.7%), Klebsiella species (13.3%), and Escherichia coli (11.1%). Gram-positive isolates were most sensitive to vancomycin (65.0%), gentamicin (65.0%), and amikacin (58.0%). Among Gram-negative isolates, Pseudomonas species showed the highest susceptibility to colistin and piperacillin-tazobactam (87.5%). In contrast, Klebsiella species showed susceptibility to imipenem, amikacin, and colistin (83.3%), and Escherichia coli showed susceptibility to imipenem (100.0%). Cephalosporin generally demonstrated limited activity.Conclusion: In conclusion, Staphylococcus aureus and Pseudomonas species are the predominant pathogens in wound infections.Bangladesh Journal of Infectious Diseases, June 2025;12(1):52-56